Calcium-Phosphate Nanoparticles — a System for Drug Delivery to the Anterior Eye Chamber - O. V. Beznos; V. E. Tikhomirova; E. V. Popova; T. A. Pavlenko; O. A. Kost; N. B. Chesnokova (Oftalʹmologiâ)
Purpose: to prepare and characterize calcium-phosphate nanoparticles loaded with compounds of different nature: low-molecular inhibitor of angiotensin-converting enzyme lisinopril, and high-molecular enzyme superoxide dismutase 1. To estimate the possibility of enhancing the biological efficacy of these compounds via incorporation to the nanoparticles.Material and methods. To increase the stability of calcium-phosphate nanoparticles coating with β-D-cellobiose was used. The size, surface charge (ζ-potential) of the particles and efficacy of including of the selected compounds to the particles were measured. Comparative assessment of the efficacy of lisinopril solution and lisinopril in nanoparticles was made via the estimation of their ocular hypotensive effect in normotensive rabbits. To compare the efficacy of the superoxide dismutase 1 solution and superoxide dismutase 1 in nanoparticles the rabbit model of immunogenic uveitis was used. We estimated the clinical score for several signs of uveitis, protein level, and antioxidant activity in aqueous humor.Results. Calcium-phosphate nanoparticles containing lisinopril had average hydrodynamic radius of 170–300 nm and negative ζ-potential of –17 mV. Particles containing superoxide dismutase 1 had average hydrodynamic radius of 220–450 nm and negative ζ-potential of –4 mV. Lisinopril in nanoparticles caused a significantly greater decrease of intraocular pressure than lisinopril solution. Superoxide dismutase 1 in calcium-phosphate nanoparticles more efficiently decreased the clinical manifestations of uveitis and normalized the biochemical processes in aqueous humor than the enzyme in buffer solution.Conclusion. Incorporation of both low-molecular and high-molecular drugs to the calcium-phosphate nanoparticles enhance their bioavailability and therapeutic efficiency. The data obtained give evidence of the prospectively of the using of these nanoparticles as vehicles for the ophthalmic drugs used in eyedrops.